MicroRNA–SIRT1 crosstalk in liver diseases: molecular regulation of metabolism, inflammation, and cell survival - Amr Ali Mohamed Abdelgawwad El-Sehrawy; Safa H. Radhie; Mirza R. Baig; Djaloliddin Mansurov; Rekha M. M.; Priya Priyadarshini Nayak; Neeraj Bainsal; Divya Singhal; Aseel Smerat; Mohammed Jawad Alnajar (Molecular Biology Reports, 2026)

Integrated genome-wide association study (GWAS) and metabolomics identify genetic and metabolic drivers of stripe rust resistance in wheat from the Western Himalayas - Farkhandah Jan; M. Parthiban; Sofora Jan; Anjan Kumar Pradhan; Sundeep Kumar; Safoora Shafi; Mahpara Bashir; Divya Sharma; Naeela Qureshi; Manish Kumar Vishwakarma; Sarabjit Kaur; Jaspal Kaur; et al. (Functional & Integrative Genomics, 2026)

Standardization of artificial inoculation technique for foot rot of finger millet caused by Sclerotium rolfsii and its validation using qPCR-based pathogen quantification - M. Bharath; H. R. Raveendra; Ravichandra; Mantesh Muttappagol; N. Sagar; Shadab M. Katib; Akash Bevanur; P. Yashwanth; Gutha Venkata Ramesh; Divya Bhandhari (Journal of Plant Pathology, 2026)

Plant-Mediated CuO Nanoparticles for Reactive Orange Dye Adsorption: Experimental study and Machine Learning-Assisted Optimization - S. Murugeshwari; Madhan Gunasekaran; B. Senthil Rathi; R. M. Saravana Kumar; J. Divya (Water, Air, & Soil Pollution, 2026)

Axial behavior of circular concrete composites confined with concrete canvas and GFRP - V. M. SharanKarthick; S. Divya; N. Shanmugasundaram; S. Praveen Kumar (Innovative Infrastructure Solutions, 2026)

Genomic cognizance of native strains of antagonistic Trichoderma asperellum from rice fields in India - Sowmya Vanama; Neha Attal; Kalyani M. Barbadikar; Maruthi Pesari; Divya Kattupalli; Raman Meenakshi Sundaram; Kannan Chinnaswami (European Journal of Plant Pathology, 2026)

Polar Winter Processes: An Under-Represented Research Focus within the Coupled Earth System - Xin Yang; Xiangdong Zhang; Ankit Agarwal; Rajendran Shobha Ajin; Thomas J. Bracegirdle; Peter Convey; Rainette Engbers; Markus M. Frey; Eugenia M. Garbarini; Irina Gorodetskaya; Xianda Gong; Sergi González-Herrero; et al. (Advances in Atmospheric Sciences, 2026)
Observing winter processes during the extended cold season is crucial not only for understanding polar and global coupled Earth system but also for enhancing capability of year-round prediction, especially in the context of Arctic amplification and the drastic decrease in sea ice extent and thickness at both poles. However, harsh environmental conditions and logistical challenges have left polar winter Earth system processes substantially under-observed compared with those during summer. This disparity creates major obstacles for studying these processes and their roles in shaping the state and variability of the Earth systems, as well as for accurately simulating them in Earth System Models (ESMs). Consequently, these limitations introduce considerable uncertainties in ESMs regarding the understanding, prediction, and projection of Earth system variability and changes. This study discusses key polar winter processes and evaluates critical knowledge gaps. It identifies three urgent research priorities for the near future: (i) sources, properties, and transport of polar winter aerosols and their interactions with clouds; (ii) polar storms and their interactions with the underlying sea ice and ocean; and (iii) persistent discrepancies in understanding and predicting large-scale teleconnections between polar regions and lower latitudes. To address these priorities, this perspective recommends strengthening coordinated, winter-focused, international and multidisciplinary observational efforts, for example, through initiatives such as the Fifth International Polar Year and the ongoing international Antarctica InSync programme. These initiatives would lay groundwork for designing future sustainable winter process observations.

Pollinia storage and viability assessment in Decalepis arayalpathra - S. Gokul; R. K. Divya; Anup S. Deshpande; P. Ravichandran; K. Ravikumar; M. K. Janarthanam; P. E. Rajasekharan; Pradeep Kumar Vishwakarma (Palynology, 2026)

Intraspecific Variation of Edwardsiella anguillarum From Non‐Anguillid Fish From Varied Geographic Origins - Abigail R. Armwood; Divya Rose; Geoffrey C. Waldbieser; Ethan Woodyard; Bradley M. Richardson; Esteban Soto; Cynthia B. Stine; Cynthia C. Ware; Paola Barato; Alvin C. Camus; Matt J. Griffin (Journal of Fish Diseases, 2026)
Edwardsiella anguillarum is a gram‐negative bacterium, synonymous with previously described atypical, fish‐pathogenic Edwardsiella tarda . Originally described from eels in 2015, E. anguillarum is an important global fish pathogen, particularly in tilapia. This study describes intraspecific phenotypic and genotypic variability among 17 E. anguillarum isolates from non‐anguillid fish hosts and varied geographic origins. Isolates demonstrated similar biochemical characteristics, with slight variation in motility and hydrogen sulfide production. Genomic relatedness among isolates was analysed with repetitive extragenic palindromic sequence‐based PCR (rep‐PCR) and multilocus sequence analysis (MLSA). Rep‐PCR with the ERIC II primer set revealed two distinct genetic clusters, while amplification strategies utilising the GTG 5 , BOX or ERIC I&II primer sets yielded more uniform profiles. While rep‐PCR deemed the isolates largely clonal, MLSA schemes using reference genes from published Edwardsiella MLSA studies revealed E. anguillarum isolates formed five discrete phylogroups. A unique, ~91.5 kB plasmid was identified in Costa Rican and Colombian isolates, associated with conjugative and transposable elements, plasmid mobilisation, and adhesion; however, no plasmid mediated antibiotic resistance genes were identified. This study provides insight into genetic diversity among E. anguillarum isolates from different hosts and geographic regions, identifying an optimal MLSA scheme from previous reports applicable to E. anguillarum isolates.

Prebreeding using untapped rice genetic resources: linking the gap between biodiversity and crop improvement - Santhosh Venna; Divya Balakrishnan; P. K. Singh; B. Arun; Suneetha Kota; S. Amurutha Rao; Naresh Kumar Sahu; S.V. SaiPrasad; R. M. Sundaram (Journal of Crop Science and Biotechnology, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Biophysical basis and morphological traits conferring resistance to yellow stem borer, Scirpophaga incertulas (walker) in land races of rice (Oryza sativa L.) - Divya D. Mallesh; Vijaykumar Lingaraj; B. Shivanna; Reddy C. N. Lakshminarayana; M. S. Kitturmath; H. R. Raveendra; K. R. Ashoka (International Journal of Tropical Insect Science, 2026)

Stomatal and leaf hydraulic conductivity responses to changing light and CO2 conditions in Phaseolus vulgaris - Andrew Ogolla Egesa; Divya Rana; Jessica Barrera-Solis; William M. Hammond; C. Eduardo Vallejos; Kevin Begcy (Plant Science, 2026)

Myelin oligodendrocyte glycoprotein antibody disease (MOGAD) with leukodystrophy-like presentation in an adult - Sreeja Samineni; Divya M. Radhakrishnan; Ajay Garg; Divyani Garg; Ayush Agarwal (Acta Neurologica Belgica, 2026)

Host plant mediated differences on biotic potential and nutritional indices of fall armyworm, Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae) - Sruthi K. K; S. Ramesh Babu; Beerendra Singh; M. L. Ojha; Khushi Saini; Divya Kumari Dhaka; Divyansh Daniel George (Phytoparasitica, 2026)

Global manta and devil ray population declines: Closing policy and management gaps to reduce fisheries mortality - Betty J.L. Laglbauer; Nidhi G. D'Costa; Joshua D. Stewart; Marta D. Palacios; Melissa Cronin; Daniel Fernando; Nerea Lezama-Ochoa; Asia O. Armstrong; Rima W. Jabado; Sarah Fowler; Julia M. Lawson; Olga Koubrak; et al. (Biological Conservation, 2026)

Toxicity and antiproliferative activity assessment of a novel compound Zr I isolated from Zingiber roseum Rosc - Swarnalatha P.; Deepika Divya K.; Anjali Jha; Anitha M.; S. P. D. Ponamgi; Seema Kumari; Sujatha Peela (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Chemical characterization and anticancer evaluation of Indian traditional rice Cultivars: Insights into their therapeutic potential - M. Udayamathi; P. Mohanapriya; S. Mahalakshmi; T. Subashini; S. Divya Sri; S. Pramila; A. Saravana Raj; Yuvaraj Dinakarkumar (Bioactive Carbohydrates and Dietary Fibre, 2025)

Wild species Oryza rufipogon as a potential donor for development of interspecific backcross population in the background of Samba Mahsuri (BPT5204) and detection of yield enhancing QTLs - M. Sridhar; C. Gireesh; Divya Balakrishnan; M. Sujatha; M. S. Anantha; C. H. Raveendra; P. Senguttuvel; D. Srinivasa Chary; V. P. Bhadana; R. M. Sundaram (Plant Physiology Reports, 2025)

Unraveling allelic variations and population structure in wild species and cultivars of rice (Oryza spp.) for yield-related genes - Musku Sridhar; Divya Balakrishnan; M. S. Anantha; P. Senguttuvel; R. M. Sundaram; L. V. Subbarao; D. Aleena; Ch. Raveendra; S. Rathod; S. R. Chimmli; G. Padmavathi; M. Sujatha; et al. (Cereal Research Communications, 2025)

Comparison of clinical, radiological and outcome parameters in patients with progressive multifocal leukoencephalopathy (PML) with and without HIV infection: a cohort study - Farsana Mustafa; Anuj Ajayababu; Ajay Garg; Megha Brijwal; Divyani Garg; Manish Soneja; Aashish Choudhary; Lalit Dar; Shariq A. Shah; Venugopalan Y Vishnu; Animesh Ray; Neeraj Nischal; et al. (Journal of NeuroVirology, 2025)

Curcumin in feed lowers leptin and its receptor gene expression, alters fatty acid and amino acid profiles and improves the antioxidant activities in the muscle of tilapia, Oreochromis mossambicus - M. V. Sruthi; Divya Lekha (Aquaculture International, 2025)

Genetic Diversity and Population Structure Analysis in Avocado (Persea americana) Accessions of India - B. M. Muralidhara; T. Sakthivel; D. C. Lakshmana Reddy; G. Karunakaran; V. Venkatravanappa; Siddanna Savadi; Divya Vani Vaka; Ponnam Naresh; K. S. Shivashankara; R. Venugopalan; M. K. Honnabyraiah (Agricultural Research, 2025)

From sea to cell: Investigating the potential health impacts of marine plastic pollution in the Philippines - Jasmine Santos; Beatrice Schleupner; Sophia Vincoff; Divya Dayanidhi; Ricardo Alindayu; Meagan M. Dunphy-Daly; William C. Eward; Jason A. Somarelli (Marine Pollution Bulletin, 2025)

Multi-environmental and multi-trait evaluation of elite finger millet genotypes for blast resistance using GGE biplot and stability analysis - Farooqkhan; K.B. Palanna; Gutha Venkata Ramesh; Prasanna S. Koti; H.R. Raveendra; T.S.S.K. Patro; Divya Bhandhari; Gandikota Brahmani; Prahlad Netam; Sujatha Bhat; H.E. Patil; Shaik Abdul Salam; et al. (Physiological and Molecular Plant Pathology, 2025)

Comparative fitness of oleander aphid, Aphis nerii Boyer de fonscolombe (Hemiptera: Aphididae) on selected medicinal hosts using an age-stage, two-sex life table - K. T. Shivakumara; M. C. Keerthi; A. C. Polaiah; S. S. Udikeri; C. Divya; K. Swapnarani (International Journal of Tropical Insect Science, 2025)

Frequency of γ-H2AX foci, micronucleus formation, and radiation dose to the blood lymphocytes in pediatric and adult participants underwent computed tomography imaging - Divya K. Mohan; Nandhini K.; Aishwarya S.; Senthil Kumar M.; Swetha K.; Akshaya J.; Sudha Pattan; Venkata Sai P.M.; Venkateswarlu Raavi; Venkatachalam Perumal (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2025)

Harnessing inter-subspecific genetic variability for hybrid rice improvement: analysis of genetic diversity, heterosis, and combining ability - K. Sruthi; K. B. Eswari; Ch. Damodar Raju; M. Sheshu Madhav; A. Dhandapani; M. Bala Satya Sree; K. Srikrishna Latha; P. Koteswararao; M. Sadath Ali; Divya Balakrishnan; P. Senguttuvel; Revathi Ponnuswamy; et al. (Euphytica, 2025)

Marker Assisted Introgression and Evaluation of Retinol Equivalent Carotenoid in the Elite Cultivars Background from Traditional Landrace ‘Kavuni’ - Suvarna Rani Chimmili; G. Subashini; M. Raveendran; C. R. Anandakumar; Jyothi Badri; Divya Balakrishnan; S. Robin (Agricultural Research, 2025)

Surviving deadly radiation: Lessons from tardigrades - Swati Ghosh; Divya Vishnu; Shravani Pillanjinayya; Sandeep M Eswarappa (Journal of Biosciences, 2025)

The effect of α-tocopherol (vitamin E) on the phase behaviour of fully-hydrated dioleoyl phosphatidylcholine membranes - Chi Long Chan; Divya Malia; Miguel Paez-Perez; Laurent Sagalowicz; Olivier Schafer; Robert V. Law; Nicholas J. Brooks; John M. Seddon (Chemistry and Physics of Lipids, 2025)

Systematic revision of the genus Orchidasma Looss, 1900 and description of Orchidasma orchilobata n. sp. from the loggerhead Caretta caretta (L.) and Kemp’s ridley Lepidochelys kempii (Garman) turtles - Thomas G. Rosser; Aiden Meaux; Ethan T. Woodyard; Justin M. Stilwell; Bradley M. Richardson; Logan R. S. Robison; Jill B. Hudnall; Kaylin McNulty; Jonah A. Nguyen; Divya Rose; Debra Moore; Beth Peterman; et al. (Systematic Parasitology, 2025)

Bryophyllum pinnatum (L.) Pers. Modulates Multiple Neuroprotective Targets in Alzheimer’s Disease: Evidence from Computational and Experimental Validation - Laxmi Pattanashetti; Manoj M. Donagannavar; Divya Jigalur; Vishal S. Patil (Cell Biochemistry and Biophysics, 2025)

Treatment of Chlorinated Volatile Organic Compounds Using Different Bioreactor Systems: Microbial Communities and Pollutant Removal - Divya Baskaran; Shishir Kumar Behera; Biswanath Mahanty; Mansi Aliveli; Amira Elmanadely; Abubakar M. Bilyaminu; Anina James; Eldon R. Rene; Ravi Rajamanickam (Water, Air, & Soil Pollution, 2025)

Separating Historical Catches Among Pygmy Blue Whale Populations Using Recent Song Detections - Trevor A. Branch; Cole C. Monnahan; Emmanuelle C. Leroy; Fannie W. Shabangu; Ana Širović; Salvatore Cerchio; Suaad Al Harthi; Cherry Allison; Naysa Balcázar Cabrera; Dawn R. Barlow; Susannah V. Calderan; Michael C. Double; et al. (Marine Mammal Science, 2025)
In the Southern Hemisphere and northern Indian Ocean, there are at least five populations of pygmy blue whales, Balaenoptera musculus brevicauda , residing in the Northwest Indian Ocean (NWIO, Oman), central Indian Ocean (CIO, Sri Lanka), Southwest Indian Ocean (SWIO, Madagascar to Subantarctic), Southeast Indian Ocean (SEIO, Australia to Indonesia), and Southwest Pacific Ocean (SWPO, New Zealand). Each population produces a distinctive repeated song, but none have population assessments or reliable measures of historical whaling pressure. Here we created pygmy blue whale catch time series by removing Antarctic blue whale catches using length data and then fitting generalized additive models (based on latitude, longitude, and month) to contemporary song data (largely from 1995 to 2023) to allocate historical catches to the five populations. Most pygmy blue whale catches (97% of 12,207) were taken by Japanese and Soviet operations during 1959/1960 to 1971/1972, with the highest totals taken from the SWIO (6514), SEIO (2593), and CIO (2023), and lower catches from the NWIO (549) and SWPO (528). The resulting predicted annual catch assignments provide the first indication of the magnitude of whaling pressure on each population and are a key step toward assessing the status of these five pygmy blue whale populations.

Co-delivery of Exemestane and Genistein via Chitosan Coated Liposomes for Enhanced Antitumor Effect and Bone Loss Prevention in Breast Cancer Therapy: In Vivo Evaluation - Shwetakshi Sharma; S. M. Kawish; Priya Gupta; Shreshta Jain; Shahnawaz Ahmad; Zeenat Iqbal; Divya Vohora; Kanchan Kohli (AAPS PharmSciTech, 2025)

High-dimensional mediation analysis to elucidate the role of metabolites in the association between PFAS exposure and reduced SARS-CoV-2 IgG in pregnancy - Haibin Guan; Jia Chen; Kirtan Kaur; Bushra Amreen; Corina Lesseur; Georgia Dolios; Syam S. Andra; Srinivasan Narasimhan; Divya Pulivarthi; Vishal Midya; Lotje D. De Witte; Veerle Bergink; et al. (Science of The Total Environment, 2025)

Performance evaluation of existing and advanced processes for remediation of microplastics: A comprehensive review - Divya P. Barai; Swati L. Gajbhiye; Yogeshwary M. Bhongade; Hemant S. Kanhere; Dadasaheb M. Kokare; Nishikant A. Raut; Bharat A. Bhanvase; Sanjay J. Dhoble (Journal of Environmental Chemical Engineering, 2025)

Unveiling the Macrofouling Communities of the Lakshadweep Archipelago, Indian Ocean: A Preliminary Study - Mohammed Siyad P.V.P.; Davood Nihal; Divya Alex M; Prabhakaran M.P (Thalassas: An International Journal of Marine Sciences, 2025)

Assessing the fluoride toxicity, and the source contributors to the major ionic constituents in the groundwater aquifer of Middle Ganga River Basin, Rohtas, India - Divya; M. A. Sulaiman; M. M. Zafar; A. Kumari (International Journal of Energy and Water Resources, 2025)

Evaluation of Eclipta alba L. selections for higher biomass and bioactive compound - K. Hima Bindu; K. Keshav Rao; Shiva Kumar; B. Anil Kumar; R. M. Shalini; Priti Sonavane; K. S. Divya; S. Sujatha (Genetic Resources and Crop Evolution, 2025)

Deep Learning in Analyzing Carbon Flux Patterns for Environmental Health: Remote Sensing Insights for Climate Mitigation Strategies - Hariharan Subramani; M. Neela Harish; Selva kumar S; P. Radhakrishnan; L. N. K. Sai Madupu; Kasturi Sai Sandeep; Divya Nimma (Remote Sensing in Earth Systems Sciences, 2025)

Sustainable Agriculture in Food Security Integrating Satellite Data Risk Assessment by Cyberattack Detection: AI Applications - M. Prema Kumar; N. Krishnammal; Manu Gupta; Mairaj Unisa Begum; Sameera Sultana; Divya Priya Degala (Remote Sensing in Earth Systems Sciences, 2025)

Effect of integrated disease management modules against major diseases (bacterial blight/root rot and downy mildew) of opium poppy - Shivam Singh; R. S. Mishra; S. K. Singh; M. K. Maurya; J. R. Yadav; Divya Singh; Abhishek Kumar; V. V. Raghuvanshi (Vegetos, 2025)

Preventing lifestyle disorders: The diet shift in India - M. Udayamathi; S. Divya Sri; S. Pramila; M. Ganesh; Yuvaraj Dinakarkumar (Food and Humanity, 2025)

Natural products as drug leads: exploring their potential in drug discovery and development - Kuldeep Singh; Jeetendra Kumar Gupta; Dilip Kumar Chanchal; Manoj Gangadhar Shinde; Shivendra Kumar; Divya Jain; Zainab M. Almarhoon; Asma M. Alshahrani; Daniela Calina; Javad Sharifi-Rad; Anjali Tripathi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Corrigendum to “Characterization of renewable material from biowaste: Waste Albizia lebbeck leaves biomass-based bioplasticizer for futuristic applications” [J. Environ. Chem. Eng. 13 (2025) 115195] - Divya Divakaran; Indran Suyambulingam; Sunesh Narayanaperumal; P. Senthamaraikannan; H. Jeevan Rao; Thiago F. Santos; Caroliny M. Santos (Journal of Environmental Chemical Engineering, 2025)

Wild introgression lines of Oryza nivara as potential donor for yield and seedling vigour traits and mapping associated genomic regions - D. Sai Teja; Divya Balakrishnan; P. Magudeeswari; Sonali Kar; P. Arun Kumar; G. Pranay; R. Pushpa; Kalyani M. Barbadikar; L. V. Subba Rao; N. Sarla; S. V. SaiPrasad; R. M. Sundaram (Euphytica, 2025)

From cognition to economic valuation of cultural ecosystem services – An evidence from Parambikulam tiger reserve, Kerala - Divya Soman; V. Anitha; Syam Viswanath; M. Sreeraj (Journal for Nature Conservation, 2025)

Retraction Note: Structural characterization of Bacillus licheniformis Dahb1 exopolysaccharide—antimicrobial potential and larvicidal activity on malaria and Zika virus mosquito vectors - Muthukumar Abinaya; Baskaralingam Vaseeharan; Mani Divya; Sekar Vijayakumar; Marimuthu Govindarajan; Naiyf S. Alharbi; Jamal M. Khaled; Mohammed N. Al-anbr; Giovanni Benelli (Environmental Science and Pollution Research, 2025)

Allometric scaling and carbon sequestration in agroforestry species of the Western Himalayas: a model-based approach - Megha VR; R. Kaushal; Sadikul Islam; Uday Mandal; Harsh Mehta; Rajkumar; J. M. S. Tomar; Anand Kumar Gupta; Anupam Barh; Vishwal Madhav P; Vibha Singhal; Rajiv Pandey; et al. (Environmental Monitoring and Assessment, 2025)

Characterization of renewable material from biowaste: Waste Albizia lebbeck leaves biomass-based bioplasticizer for futuristic applications - Divya Divakaran; Indran Suyambulingam; Sunesh Narayanaperumal; P. Senthamaraikannan; H. Jeevan Rao; Thiago F. Santos; Caroliny M. Santos (Journal of Environmental Chemical Engineering, 2025)

Characterizing metabolome signature of colostrum, transition and mature milk of indigenous cows (Bos indicus) adapted to high altitude environment of Leh-Ladakh - Amarjeet; Umesh Kumar; Monika Sodhi; Dinesh Kumar; Prince Vivek; Saket K. Niranjan; Ranjit Singh Kataria; Sudarshan Kumar; Manish Sharma; Manish Tiwari; Rajeev A.K. Aggarwal; Vijay K. Bharti; et al. (Food Chemistry, 2025)

A spatially explicit assessment of factors shaping attitudes toward African elephant conservation - Sarah L. Carroll; Susanne M. Vogel; Purity Nititi Taek; Clevers Tumuti; Divya Vasudev; Varun R. Goswami; Jake Wall; Stephen Mwiu; Robin S. Reid; Jonathan Salerno (Conservation Biology, 2025)
Conservation plans that explicitly account for the social landscape where people and wildlife co‐occur can yield more effective and equitable conservation practices and outcomes. Yet, social data remain underutilized, often because social data are treated as aspatial or are analyzed with approaches that do not quantify uncertainty or address bias in self‐reported data. We conducted a survey (questionnaires) of 177 households in a multiuse landscape in the Kenya–Tanzania borderlands. In a mixed‐methods approach, we used Bayesian hierarchical models to quantify and map local attitudes toward African elephant ( Loxodonta africana ) conservation while accounting for response bias and then combined inference from attitude models with thematic analysis of open‐ended responses and cointerpretation of results with local communities to gain deeper understanding of what explains attitudes of people living with wildlife. Model estimates showed that believing elephants have sociocultural value increased the probability of respondents holding positive attitudes toward elephant conservation in general (mean increase = 0.31 [95% credible interval, CrI, 0.02–0.67]), but experiencing negative impacts from any wildlife species lowered the probability of respondents holding a positive attitude toward local elephant conservation (mean decrease = −0.20 [95% CrI −0.42 to 0.03]). Qualitative data revealed that safety and well‐being concerns related to the perceived threats that elephants pose to human lives and livelihoods, and limited incentives to support conservation on community and private lands lowered positive local attitude probabilities and contributed to negative perceptions of human–elephant coexistence. Our spatially explicit modeling approach revealed fine‐scale variation in drivers of conservation attitudes that can inform targeted conservation planning. Our results suggest that approaches focused on sustaining existing sociocultural values and relationships with wildlife, investing in well‐being, and implementing species‐agnostic approaches to wildlife impact mitigation could improve conservation outcomes in shared landscapes.

Novel Ti/rGO@ZnCr LDH derived MMO for photocatalytic conversion of atmospheric elements and organic pollutants into valuable resources - Prabagar Jijoe Samuel; Tenzin Thinley; Divya Vinod; Hosakote Shankara Anusha; Hemanth Vikram P R; Gurupadayya B M; Kotermane Mallikarjunappa Anilkumar; Manickam Selvaraj; Mohammed A. Assiri; Harikaranahalli Puttaiah Shivaraju (Journal of Environmental Chemical Engineering, 2024)

The role of rural circular migration in shaping weather risk management for smallholder farmers in India, Nepal, and Bangladesh - Divya Solomon; Asif Ishtiaque; Arun Agarwal; Joshua M. Gray; Maria Carmen Lemos; Ignatius Moben; Balwinder Singh; Meha Jain (Global Environmental Change, 2024)

Trends in pancreatic cancer mortality in the United States 1999–2020: a CDC database population-based study - Alexander J. Didier; Swamroop Nandwani; Alan M. Fahoury; Daniel J. Craig; Dean Watkins; Andrew Campbell; Caleb T. Spencer; Macelyn Batten; Divya Vijendra; Jeffrey M. Sutton (Cancer Causes & Control, 2024)
Introduction Pancreatic cancer is a significant public health concern and a leading cause of cancer-related deaths worldwide. This study aimed to investigate pancreatic cancer mortality trends and disparities in the United States (US) from 1999 to 2020. Methods Data were obtained from the Centers for Disease Control (CDC) Wide-Ranging Online Data for Epidemiologic Research database. Mortality rates were age-adjusted and standardized to the year 2000 US population. Joinpoint regression was used to analyze temporal trends in age-adjusted mortality rates (AAMRs) by sociodemographic and geographic variables. Results Between 1999 and 2020, pancreatic cancer led to a total of 810,628 deaths in the US, an average mortality of nearly 39,000 deaths per year. The AAMR slightly increased from 10.6 in 1999 to 11.1 in 2020, with an associated annual percent change (APC) of 0.2. Mortality rates were highest among individuals aged 65 and older. Black individuals experienced the highest overall pancreatic cancer-related AAMR at 13.8. Despite this, Black individuals experienced a decreasing mortality trend over time (APC −0.2) while White individuals experienced an increasing trend in mortality (APC 0.4). Additionally, individuals residing in rural areas experienced steeper rates of mortality increase than those living in urban areas (APC 0.6 for rural vs −0.2 for urban). White individuals in urban and rural populations experienced an increase in mortality, while Black individuals in urban environments experienced a decrease in mortality, and Black individuals in rural environments experienced stable mortality trends. Conclusions Mortality from pancreatic cancer continues to increase in the US, with racial and regional disparities identified in minorities and rural-dwelling individuals. These disparate findings highlight the importance of ongoing efforts to understand and address pancreatic cancer treatment and outcomes disparities in the US, and future studies should further investigate the underlying etiologies of these disparities and potential for novel therapies to reduce the mortality.

Remote Sensing–Based UAV Imaging in Heat Pattern Analysis Impact on Climate Change Detection Using Fuzzy Stacked Lasso Elastic-Net Model - M. Sailaja; M. Prema Kumar; B. Swarna Jyothi; G. L. Narasamba Vanguri; S. Manjula; D. Divya Priya (Remote Sensing in Earth Systems Sciences, 2024)

Geospatial assessment of agroforestry land use systems using very high-resolution satellite images and artificial intelligence - Shivam Trivedi; P. V. Vinod; B. Chandrasekaran; M. K. Nagashree; S. Rama Subramoniam; V. B. Manjula; Amrita Singh; J. K. Mani; Arun S. Suryavanshi; Sushilkumar B. Rehpade; Akash Goyal; N. R. Shankar Ram; et al. (Agroforestry Systems, 2024)

Application of artificial intelligence tools in wastewater and waste gas treatment systems: Recent advances and prospects - Shishir Kumar Behera; S. Karthika; Biswanath Mahanty; Saroj K. Meher; Mohd. Zafar; Divya Baskaran; Ravi Rajamanickam; Raja Das; Kannan Pakshirajan; Abubakar M. Bilyaminu; Eldon R. Rene (Journal of Environmental Management, 2024)

Assessment of species migration patterns in forest ecosystems of Tamil Nadu, India, under changing climate scenarios - Ramachandran A.; Mithilasri Manickavasagam; Hariharan S.; Mathan M.; Ahamed Ibrahim S.N.; Divya Subash Kumar; Kurian Joseph (Theoretical and Applied Climatology, 2024)

Head Impact Kinematics and Brain Tissue Strains in High School Lacrosse - Declan A. Patton; Colin M. Huber; Divya Jain; Svein Kleiven; Zhou Zhou; Christina L. Master; Kristy B. Arbogast (Annals of Biomedical Engineering, 2024)

Enhancing milk quality assessment with watermelon (Citrullus lanatus) urease immobilized on VS2-chitosan nanocomposite beads using response surface methodology - Prince Kumar; Divya; Amit Kumar Patel; Anchal Srivastava; Arvind M. Kayastha (Food Chemistry, 2024)

Efficacy of biological agent Lecanicillium lecanii for the management of coffee leaf rust in India - Divya K. Das; Santoshreddy Machenahalli; Madhu S. Giri; Ranjini A. P; N. Suryaprakash Rao; M. B. Shivanna (Indian Phytopathology, 2024)

Multi-environment testing revealed the effect of yield genes on the grain yield stability in diverse rice germplasm - Aleena Dasari; Divya Balakrishnan; Santosha Rathod; P. V. R. Rao; Laksminarayana R. Vemireddy; C. N. Neeraja; S. Vanisri; K. N. Ranjith; R. M. Sundaram; Jyothi Badri (Cereal Research Communications, 2024)

Linkage mapping and quantitative trait loci detection for seedling vigor and grain size in advanced backcross introgression lines from wild accessions of Oryza nivara - P. Magudeeswari; Divya Balakrishnan; Yoshimichi Fukuta; Hiroki Saito; D. Saitheja; G. Pranay; R. Padmashree; Kalyani M Barbadikar; Jyothi Badri; P. Senguttuvel; K. Sruthi; D. Ladhalakshmi; et al. (Genetic Resources and Crop Evolution, 2024)

Morphological and molecular data establishes Clinostomum dolichorchum n. sp. (Digenea: Clinostomidae) in the great blue heron Ardea herodias L. and American bullfrog Rana catesbeiana Shaw - Jonah A. Nguyen; Ethan T. Woodyard; Chris T. McAllister; Susan V. Marcquenski; Divya Rose; Celene M. Slifka; Logan R. S. Robison; Matt J. Griffin; T. Graham Rosser (Systematic Parasitology, 2024)

Fine mapping of interspecific secondary CSSL populations revealed key regulators for grain weight at qTGW3.1 locus from Oryza nivara - Malathi Surapaneni; Divya Balakrishnan; Krishnamraju Addanki; Venkateswara Rao Yadavalli; Arun Prem Kumar; P. Prashanthi; R. M. Sundaram; Sarla Neelamraju (Physiology and Molecular Biology of Plants, 2024)

Metal organic frameworks: Building blocks for a greener future - Dhamodharan Duraisami; Mamdouh Ahmed Al-Harthi; Ramya B; Divya Baskaran; Elakkiya M; Abdullah Bafaqeer (Journal of Cleaner Production, 2024)

Development of polymorphic microsatellite markers for genetic stock identification of green chromide, Etroplus suratensis using next generation sequencing technology - Magdeline Christo; Divya Merin Jose; P. R. Divya; M. U. Rekha; U. K. Sarkar (Conservation Genetics Resources, 2024)

Restoration opportunities beyond highly degraded tropical forests: Insights from India's Western Ghats - Anand M. Osuri; Srinivasan Kasinathan; T.R. Shankar Raman; Divya Mudappa (Biological Conservation, 2024)

Biometeorological analysis on the molecular incidence of babesiosis and ehrlichiosis in dogs - Y. Ajith; Sasi Adithya; Varuna P. Panicker; N. Athira; V. Beena; M. Saifudeen Safeer; P. Preena; A. R. Nisha; C. Divya; S. G. Sangeetha; C. G. Umesh; R. C. Sundararajan; et al. (Theoretical and Applied Climatology, 2024)

Mapping QTLs for grain iron, zinc, and yield traits in advanced backcross inbred lines of Samba mahsuri (BPT5204)/Oryza rufipogon - Gowthami Chandu; Divya Balakrishnan; Suchandranath Babu Munnam; Satendra K. Mangrauthia; Durbha Sanjeeva Rao; C. N. Neeraja; R. M. Sundaram; Sarla Neelamraju (Journal of Plant Biochemistry and Biotechnology, 2024)

Low clouds over the subtropical Indian Ocean and sub-seasonal circulation associations with the Indian summer monsoon - T. Gokul; R. K. Vellore; D. C. Ayantika; V. Divya; R. Krishnan; M. J. K. Reji (Climate Dynamics, 2024)

Diversity of Indian rice cultivars and landraces for seedling vigour and their association for yield related traits - Sai Teja Dayala; Divya Balakrishnan; Sonali Kar; J. L. Ganguli; L. V. Subba Rao; R. M. Sundaram (Vegetos, 2024)

Hybrid extraction distillation for downstream purification of 2, 3-butanediol, and ethanol from fermentation broth - Pramod M. Gawal; Divya Mudgil; Sanjukta Subudhi (Bioresource Technology Reports, 2023)

Meta-QTL analysis in wheat: progress, challenges and opportunities - Divya Sharma; Anita Kumari; Priya Sharma; Anupma Singh; Anshu Sharma; Zahoor Ahmad Mir; Uttam Kumar; Sofora Jan; M. Parthiban; Reyazul Rouf Mir; Pradeep Bhati; Anjan Kumar Pradhan; et al. (Theoretical and Applied Genetics, 2023)

Identification and validation of blast resistance Pi1 gene in the derived mapping population of rice variety, NLR34449 through molecular markers - Dasari Aleena; V. Padma; G. Rekha; M. S. Prasad; M. S. Madhav; E. Punniakoti; T. Dilip; P. Sinha; M. Kousik; M. A. Das; M. Anila; Lal Ahmmed; et al. (Indian Phytopathology, 2023)

Toxicity prediction and analysis of flavonoid apigenin as a histone deacetylase inhibitor: an in-silico approach - N. Divya Rajaselvi; M. D. Jida; Devu B. Nair; S. Sujith; Nisaath Beegum; A. R. Nisha (In Silico Pharmacology, 2023)

Dealing with Environmental Fluctuations: Diversity of Potassium Uptake Systems Across the Three Domains of Life - Divya Rajagopal; Sudhir K. Sopory; M. K. Mathew (Journal of Plant Growth Regulation, 2023)

Global assessment of the biodiversity safeguards of development banks that finance infrastructure - Divya Narain; Laura J. Sonter; Alex Mark Lechner; James E. M. Watson; Jeremy S. Simmonds; Martine Maron (Conservation Biology, 2023)
Infrastructure development is a major driver of biodiversity loss globally. With upward of US$2.5 trillion in annual investments in infrastructure, the financial sector indirectly drives this biodiversity loss. At the same time, biodiversity safeguards (project‐level biodiversity impact mitigation requirements) of infrastructure financiers can help limit this damage. The coverage and harmonization of biodiversity safeguards are important factors in their effectiveness and therefore warrant scrutiny. It is equally important to examine the extent to which these safeguards align with best‐practice principles for biodiversity impact mitigation outlined in international policies, such as that of the International Union for Conservation of Nature. We assessed the biodiversity safeguards of public development banks and development finance institutions for coverage, harmonization, and alignment with best practice. We used Institute of New Structural Economics and Agence Française de Développement's global database to identify development banks that invest in high‐biodiversity‐footprint infrastructure and have over US$500 million in assets. Of the 155 banks, 42% ( n = 65) had biodiversity safeguards. Of the existing safeguards, 86% (56 of 65) were harmonized with International Finance Corporation (IFC) Performance Standard 6 (PS6). The IFC PS6 (and by extension the 56 safeguard policies harmonized with it) had high alignment with international best practice in biodiversity impact mitigation, whereas the remaining 8 exhibited partial alignment, incorporating few principles that clarify the conditions for effective biodiversity offsetting. Given their dual role in setting benchmarks and leveraging private finance, infrastructure financiers in development finance need to adopt best‐practice biodiversity safeguards if the tide of global biodiversity loss is to be stemmed. The IFC PS6, if strengthened, can act as a useful template for other financier safeguards. The high degree of harmonization among safeguards is promising, pointing to a potential for diffusion of practices.

Urban growth trend analysis of proposed Greater Silchar City, India, using landscape metrics and Shannon entropy model - Divya Prakash Mohabey; Jenita M. Nongkynrih; Upendra Kumar (Environment, Development and Sustainability, 2023)

The projected changes in extreme wave height indices over the Indian Ocean using COWCLIP2.0 datasets - Divya Sardana; Prashant Kumar; Prasad K. Bhaskaran; T. M. Balakrishnan Nair (Climate Dynamics, 2023)

Temporal variability of a soundscape near a mid-oceanic atoll in the northern Indian ocean - Divya Panicker; Kathleen M. Stafford (Progress in Oceanography, 2023)

Whole‐exome sequencing analyses in a Saudi Ischemic Stroke Cohort reveal association signals, and shows polygenic risk scores are related to Modified Rankin Scale Risk - Fahad A. Alkhamis; Majed M. Alabdali; Abdulla A. Alsulaiman; Abdullah S. Alamri; Rudaynah Alali; Mohammed S. Akhtar; Sadiq A. Alsalman; Cyril Cyrus; Aishah I. Albakr; Anas S. Alduhalan; Divya Gandla; Khaldoun Al-Romaih; et al. (Functional & Integrative Genomics, 2023)
Ischemic stroke represents a significant societal burden across the globe. Rare high penetrant monogenic variants and less pathogenic common single nucleotide polymorphisms (SNPs) have been described as being associated with risk of diseases. Genetic studies in Saudi Arabian patients offer a greater opportunity to detect rare high penetrant mutations enriched in these consanguineous populations. We performed whole exome sequencing on 387 ischemic stroke subjects from Saudi Arabian hospital networks with up to 20,230 controls from the Saudi Human Genome Project and performed gene burden analyses of variants in 177 a priori loci derived from knowledge-driven curation of monogenic and genome-wide association studies of stroke. Using gene-burden analyses, we observed significant associations in numerous loci under autosomal dominant and/or recessive modelling. Stroke subjects with modified Rankin Scale (mRSs) above 3 were found to carry greater cumulative polygenic risk score (PRS) from rare variants in stroke genes (standardized PRS mean > 0) compared to the population average (standardized PRS mean = 0). However, patients with mRS of 3 or lower had lower cumulative genetic risk from rare variants in stroke genes (OR (95%CI) = 1.79 (1.29–2.49), p = 0.0005), with the means of standardized PRS at or lower than 0. In conclusion, gene burden testing in Saudi stroke populations reveals a number of statistically significant signals under different disease inheritance models. However, interestingly, stroke subjects with mRS of 3 or lower had lower cumulative genetic risk from rare variants in stroke genes and therefore, determining the potential mRS cutoffs to use for clinical significance may allow risk stratification of this population.

A comprehensive health effects assessment of the use of sanitizers and disinfectants during COVID-19 pandemic: a global survey - Fallah Hashemi; Lori Hoepner; Farahnaz Soleimani Hamidinejad; Daniela Haluza; Sima Afrashteh; Alireza Abbasi; Elma Omeragić; Belma Imamović; Narin A. Rasheed; Taqi M. J. Taher; Fitri Kurniasari; Dhuha Youssef Wazqar; et al. (Environmental Science and Pollution Research, 2023)

N-Glycoprofiling of immunoglobulin G and lactoperoxidase from sheep milk using LC-MS/MS - M. Sudarshan; V. Divya Shree; P. Jyothibai; B.S. Gnanesh Kumar (International Dairy Journal, 2023)

Edge-of-field monitoring to assess the effectiveness of conservation practices in the reduction of carbon losses from the foothills of the Himalayas - Divya Sharma; Vikas Sharma; Tejbir S. Buttar; Arpita Sharma; Vivak M. Arya (CATENA, 2023)

Seasonal plankton dynamics in Kongsfjorden during two years of contrasting environmental conditions - Philipp Assmy; Ane Cecilie Kvernvik; Haakon Hop; Clara J.M. Hoppe; Melissa Chierici; Divya David T.; Pedro Duarte; Agneta Fransson; Laura M. García; Weronika Patuła; Sławomir Kwaśniewski; Marion Maturilli; et al. (Progress in Oceanography, 2023)

Outbreak and Management of Serpentine Leaf Miner, Liriomyza huidobrensis (Blanchard) (Diptera: Agromyzidae), on Potato (Solanum tuberosum L.) Crop in India - Priyank Hanuman Mhatre; Shivaji Hausrao Thube; Om Navik; E. P. Venkatasalam; Sanjeev Sharma; Jagadeesh Patil; S. Subhash; K. L. Divya; Santosh Watpade; Thava Prakash Pandian; M. Abas Shah; Manoj Kumar (Potato Research, 2022)

Three territory sign in COVID-19 - Prashant Bhatele; Animesh Das; Awadh Kishor Pandit; Divya M. Radhakrishnan; Achal Kumar Srivastava (Acta Neurologica Belgica, 2022)

Serum glucose-regulated protein 78 (GRP78) levels in COVID-19-associated mucormycosis: results of a case–control study - Valliappan Muthu; Manpreet Dhaliwal; Arunima Sharma; Divya Nair; H. Mohan Kumar; Shivaprakash M. Rudramurthy; Inderpaul Singh Sehgal; Hansraj Choudhary; Naresh Panda; Arunaloke Chakrabarti; Ritesh Agarwal (Mycopathologia, 2022)

In silico identification of potential inhibitors of MPS1 from edible mushroom (Pleurotus ostreatus) to prevent aneuploidy and tumorigenesis - Divya Mishra; Ashish Mishra; Pramod Katara; M. P. Singh (Journal of Proteins and Proteomics, 2022)

Yield Estimation of Cassava Using SIMCAS Model Over the Major Cassava Growing Regions in India - Divya K. Lekshmanan; Raji Pushpalatha; V. S. Santhosh Mithra; S. Sunitha; James George; M. Velmurugan; P. Ashok; N. V. Mhasker; K. D. Desai; R. Shiny; Gangadharan Byju (Agricultural Research, 2022)

Comparison of proton transfer paths to the QA and QB sites of the Rb. sphaeroides photosynthetic reaction centers - Rongmei Judy Wei; Yingying Zhang; Junjun Mao; Divya Kaur; Umesh Khaniya; M. R. Gunner (Photosynthesis Research, 2022)

Total hip replacement monitoring: numerical models for the acoustic emission technique - Remya Ampadi Ramachandran; Christine Lee; Lu Zhang; Supriya M. H; Divya Bijukumar; P. Srinivasa Pai; Kharma Foucher; Sheng-Wei Chi; Didem Ozevin; Mathew T. Mathew (Medical & Biological Engineering & Computing, 2022)

Assessment of heterotic potential and combining ability of novel iso-cytoplasmic restorer lines derived from an elite rice hybrid, KRH-2, for the development of superior rice hybrids - Swapnil Ravindra Kulkarni; S M Balachandran; R A Fiyaz; Divya Balakrishnan; K Sruthi; K Ulaganathan; A S Hari Prasad; R M Sundaram (Euphytica, 2022)

Mesenchymal Stem Cell Therapy in the Treatment of Neurodegenerative Cerebellar Ataxias: a Systematic Review and Meta-analysis - Manish Bhartiya; Amit Kumar; Rakesh K. Singh; Divya M Radhakrishnan; Roopa Rajan; Achal Kumar Srivastava (The Cerebellum, 2022)

Genetic stock identification in Perna viridis (Linnaeus1758) from the Indian Peninsula by using microsatellite markers - P. R. Divya; Linu Joy; Sunitha Poulose; P. M. Elizabeth Jency; V. S. Basheer; A. Kathirvelpandian; Vindhya Mohindra; Kuldeep Kumar Lal (Molecular Biology Reports, 2022)

Multi-criteria Decision Analysis for Site Selection of Apple Crop Cultivation: Case Study of Nainital, Uttarakhand - Priyadarshi Upadhyay; M. P. S. Bisht; Divya Uniyal (Journal of the Indian Society of Remote Sensing, 2022)

Chitosan nanoparticles as a rice growth promoter: evaluation of biological activity - K. Divya; Meenu Thampi; Smitha Vijayan; S. Shabanamol; M. S. Jisha (Archives of Microbiology, 2022)

Impact of polystyrene microplastics on major marine primary (phytoplankton) and secondary producers (copepod) - P. Raju; P. Santhanam; S. Sonai Pandian; M. Divya; A. Arunkrishnan; K. Nanthini Devi; S. Ananth; J. Roopavathy; P. Perumal (Archives of Microbiology, 2022)

Impact of the COVID-19 pandemic on agricultural production, livelihoods, and food security in India: baseline results of a phone survey - Lindsay M. Jaacks; Divya Veluguri; Rajesh Serupally; Aditi Roy; Poornima Prabhakaran; GV Ramanjaneyulu (Food Security, 2021)
The aim of this study was to evaluate the impact of the COVID-19 lockdown on agricultural production, livelihoods, food security, and dietary diversity in India. Phone interview surveys were conducted by trained enumerators across 12 states and 200 districts in India from 3 to 15 May 2020. A total of 1437 farmers completed the survey (94% male; 28% 30–39 years old; 38% with secondary schooling). About one in ten farmers (11%) did not harvest in the past month with primary reasons cited being unfavorable weather (37%) and lockdown-related reasons (24%). A total of 63% of farmers harvested in the past month (primarily wheat and vegetables), but only 44% had sold their crop; 12% were still trying to sell their crop, and 39% had stored their crop, with more than half (55%) reporting lockdown-related issues as the reason for storing. Seventy-nine percent of households with wage-workers witnessed a decline in wages in the past month and 49% of households with incomes from livestock witnessed a decline. Landless farmers were about 10 times more likely to skip a meal as compared to large farmers (18% versus 2%), but a majority reported receiving extra food rations from the government. Nearly all farmers reported consuming staple grains daily in the past week (97%), 63% consumed dairy daily, 40% vegetables daily, 26% pulses daily, and 7% fruit daily. These values are much lower than reported previously for farmers in India around this time of year before COVID-19: 94–95% dairy daily, 57–58% pulses daily, 64–65% vegetables daily, and 42–43% fruit daily. In conclusion, we found that the COVID-19 lockdown in India has primarily impacted farmers’ ability to sell their crops and livestock products and decreased daily wages and dietary diversity.

Northern Indian Ocean blue whale songs recorded off the coast of India - Divya Panicker; Kathleen M. Stafford (Marine Mammal Science, 2021)

Eumycetoma of the Foot due to Fusarium solani in a Person with Diabetes Mellitus: Report of a Case and Review of Literature - Liza Das; Divya Dahiya; Kirti Gupta; Mahesh Prakash; Bhanu Malhotra; Ashu Rastogi; Hansraj Choudhary; Shivaprakash M. Rudramurthy; Pinaki Dutta (Mycopathologia, 2021)

Renoprotective effect of tectorigenin glycosides isolated from Iris spuria L. (Zeal) against hyperoxaluria and hyperglycemia in NRK-49Fcells - Ganesan Divya; Abhishek Albert; Abdel Nasser B. Singab; Iriny M. Ayoub; Eman Al-Sayed; Eldho Paul; Kumarriah Manoharan; Luciano Saso; Govindan Sadasivam Selvam (Natural Product Research, 2021)

Development of Improved Strategies for the Survival of Lactobacillus Plantarum MTCC 1407 in Probioticated Custard Apple Juice - M. Arunkumar; S. K. Divya; N. Mahesh; S. Balakumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

Experimental Evaluation of Seaweeds Liquid Extracts as an Alternative Culture Medium on the Growth and Proximate Composition of Picochlorum maculatum - S. Bharathi; S. Dinesh Kumar; S. Sekar; P. Santhanam; M. Divya; N. Krishnaveni; M. Pragnya; B. Dhanalakshmi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

Color slices analysis of land use changes due to urbanization in a city environment of Miami Area, South Florida, USA - Y. Divya; P. Gopinathan; Krish Jayachandran; Ayad M. Fadhil Al-Quraishi (Modeling Earth Systems and Environment, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Identification of potential Mpro inhibitors for the treatment of COVID-19 by using systematic virtual screening approach - Ashish M. Kanhed; Dushyant V. Patel; Divya M. Teli; Nirav R. Patel; Mahesh T. Chhabria; Mange Ram Yadav (Molecular Diversity, 2021)

Exploring the Diversity of the Marine Environment for New Anti-cancer Compounds - Divya L. Dayanidhi; Beatrice C. Thomas; Joshua S. Osterberg; Mallissa Vuong; Giselle Vargas; Sarah K. Kwartler; Emma Schmaltz; Meagan M. Dunphy-Daly; Thomas F. Schultz; Daniel Rittschof; William C. Eward; Christopher Roy; et al. (Frontiers in Marine Science, 2021)
Marine ecosystems contain over 80% of the world’s biodiversity, and many of these organisms have evolved unique adaptations enabling survival in diverse and challenging environments. The biodiversity within the world’s oceans is a virtually untapped resource for the isolation and development of novel compounds, treatments, and solutions to combat human disease. In particular, while over half of our anti-cancer drugs are derived from natural sources, almost all of these are from terrestrial ecosystems. Yet, even from the limited analyses to date, a number of marine-derived anti-cancer compounds have been approved for clinical use, and several others are currently in clinical trials. Here, we review the current suite of marine-derived anti-cancer drugs, with a focus on how these compounds act upon the hallmarks of cancer. We highlight potential marine environments and species that could yield compounds with unique mechanisms. Continued exploration of marine environments, along with the characterization and screening of their inhabitants for unique bioactive chemicals, could prove fruitful in the hunt for novel anti-cancer therapies.

Obstructive Sleep Apnea Comorbid with Late-Onset Kleine–Levin Syndrome: A Rare Condition - M. P. Divya; Akash Kumar; Shivam Gupta; Sudheer Tale; Lokesh Kumar Saini; Ravi Gupta (Sleep and Vigilance, 2020)

Epigenetics and transgenerational memory in plants under heat stress - Arun K. Shanker; Divya Bhanu; M. Maheswari (Plant Physiology Reports, 2020)

Leaf blast disease in finger millet [Eleusine coracana (L.) Gaertn.] caused by Bipolaris sorokiniana Sacc.: a histopathological study - Pereira Preethi; M. S. Sharada; C. R. Divya (Journal of Plant Diseases and Protection, 2020)

Head Impact Sensor Studies In Sports: A Systematic Review Of Exposure Confirmation Methods - Declan A. Patton; Colin M. Huber; Divya Jain; Rachel K. Myers; Catherine C. McDonald; Susan S. Margulies; Christina L. Master; Kristy B. Arbogast (Annals of Biomedical Engineering, 2020)

Assessment of genetic diversity and development of core germplasm in durum wheat using agronomic and grain quality traits - Divya Ambati; Rahul M. Phuke; V. Vani; S. V. Sai Prasad; Jang Bahadur Singh; Chandra Prakash Patidar; Prakash Malviya; Amit Gautam; Vijay G. Dubey (Cereal Research Communications, 2020)

Purification and biochemical characterization of a novel secretory dipeptidyl peptidase IV from porcine serum - Divya Kumar; Vivek K. Hamse; K. N. Neema; Priya Babu Shubha; D. M. Chetan; Nanjunda Swamy Shivananju (Molecular and Cellular Biochemistry, 2020)

Population connectivity and genetic structure of Asian green mussel, Perna viridis along Indian waters assessed using mitochondrial markers - P. R. Divya; P. M. Elizabeth Jency; Linu Joy; A. Kathirvelpandian; Rajeev Kumar Singh; V. S. Basheer (Molecular Biology Reports, 2020)

Evaluation of genetic diversity of parental lines for development of heterotic groups in hybrid rice (Oryza sativa L.) - K. Sruthi; B. Divya; P. Senguttuvel; P. Revathi; K. B. Kemparaju; P. Koteswararao; R. M. Sundaram; Vikram Jeet Singh; E. Ranjith Kumar; Prolay Kumar Bhowmick; K. K. Vinod; S. Gopala Krishnan; et al. (Journal of Plant Biochemistry and Biotechnology, 2020)

Genetics of novel brown planthopper Nilaparvata lugens (Stål) resistance genes in derived introgression lines from the interspecific cross O. sativa var. Swarna × O. nivara - S. Akanksha; V. Jhansi Lakshmi; Arun Kumar Singh; Yamini Deepthi; P. M. Chirutkar; Ramdeen; Divya Balakrishnan; N. Sarla; S. K. Mangrauthia; T. Ram (Journal of Genetics, 2019)

Relative stability of the S2 isomers of the oxygen evolving complex of photosystem II - Divya Kaur; Witold Szejgis; Junjun Mao; Muhamed Amin; Krystle M. Reiss; Mikhail Askerka; Xiuhong Cai; Umesh Khaniya; Yingying Zhang; Gary W. Brudvig; Victor S. Batista; M. R. Gunner (Photosynthesis Research, 2019)

Tenecteplase versus alteplase in acute ischemic stroke: systematic review and meta-analysis - A. Thelengana; Divya M. Radhakrishnan; Manya Prasad; Amit Kumar; Kameshwar Prasad (Acta Neurologica Belgica, 2019)

Macromolecular properties and partial amino acid sequence of a Kunitz-type protease inhibitor from okra (Abelmoschus esculentus) seeds - Debparna Datta; Gottfried Pohlentz; Saradamoni Mondal; M Bala Divya; Lalitha Guruprasad; Michael Mormann; Musti J Swamy (Journal of Biosciences, 2019)

Preliminary Screening of Halophilic Microalgae Collected from Different Salt Pans of Tuticorin, Southeast Coast of India - S. Balakrishnan; P. Santhanam; S. Jeyanthi; M. Divya; M. Srinivasan (Proceedings of the Zoological Society, 2019)

Identification and feld evaluation of female sex pheromone of leaf-eating caterpillar, Opisina arenosella (Lepidoptera: Oecophoridae) - K. R. M. Bhanu; D. R. Hall; R. V. Awalekar; M. Chandrashekharaiah; T. N. Divya; M. S. Prabhakara; K. P. Jayanth (International Journal of Tropical Insect Science, 2018)

Overfishing and Climate Drives Changes in Biology and Recruitment of the Indian Oil Sardine Sardinella longiceps in Southeastern Arabian Sea - Vasant Kripa; Kolliyil S. Mohamed; K. P. Said Koya; R. Jeyabaskaran; D. Prema; Shelton Padua; Somy Kuriakose; P. S. Anilkumar; Preetha G. Nair; T. V. Ambrose; A. M. Dhanya; K. S. Abhilash; et al. (Frontiers in Marine Science, 2018)

Mesenchymal Stem Cells of Different Origin-Seeded Bioceramic Construct in Regeneration of Bone Defect in Rabbit - Swapan Kumar Maiti; M. U. Shivakumar; Divya Mohan; Naveen Kumar; Karam Pal Singh (Tissue Engineering and Regenerative Medicine, 2018)

RETRACTED ARTICLE: Structural characterization of Bacillus licheniformis Dahb1 exopolysaccharide—antimicrobial potential and larvicidal activity on malaria and Zika virus mosquito vectors - Muthukumar Abinaya; Baskaralingam Vaseeharan; Mani Divya; Sekar Vijayakumar; Marimuthu Govindarajan; Naiyf S. Alharbi; Jamal M. Khaled; Mohammed N. Al-anbr; Giovanni Benelli (Environmental Science and Pollution Research, 2018)

Chitosan nanoparticles preparation and applications - K. Divya; M. S. Jisha (Environmental Chemistry Letters, 2018)

Dimethylarginine dimethylaminohydrolase-1 (DDAH1) is frequently upregulated in prostate cancer, and its overexpression conveys tumor growth and angiogenesis by metabolizing asymmetric dimethylarginine (ADMA) - Karthik Reddy Kami Reddy; Chandrashekhar Dasari; Divya Duscharla; Bhukya Supriya; N. Sai Ram; M. V. Surekha; Jerald Mahesh Kumar; Ramesh Ummanni (Angiogenesis, 2018)

Estimation of Cd, Pb and flame retardants in electric mosquito bat using EDXRF, ICP-OES, AAS and GC–MS - B. Divya; S. Harish; K. Ramaswamy; M. Kishorebabu; N. Raju; R. Govindaiah; U. Rambabu; N. R. Munirathnam (International Journal of Environmental Science and Technology, 2017)

Platform model describing pharmacokinetic properties of vc-MMAE antibody–drug conjugates - Matts Kågedal; Leonid Gibiansky; Jian Xu; Xin Wang; Divya Samineni; Shang-Chiung Chen; Dan Lu; Priya Agarwal; Bei Wang; Ola Saad; Neelima Koppada; Bernard M. Fine; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

Development of an efficient high-performance thin layer chromatography method for determination of jasmonic acid in leaf tissue of Stevia rebaudiana (Bertoni) Bertoni - Divya Kilam; M. Saifi; A. Agnihotri; M. Z. Abdin (Natural Product Research, 2017)

Development and Translational Application of an Integrated, Mechanistic Model of Antibody-Drug Conjugate Pharmacokinetics - Siddharth Sukumaran; Crystal Zhang; Douglas D. Leipold; Ola M. Saad; Keyang Xu; Kapil Gadkar; Divya Samineni; Bei Wang; Marija Milojic-Blair; Montserrat Carrasco-Triguero; Bonnee Rubinfeld; Paul Fielder; et al. (The AAPS Journal, 2017)

Population-level diversity in the association of genetic polymorphisms of one-carbon metabolism with breast cancer risk - Shaik Mohammad Naushad; Chandrasekhar Divya; M. Janaki Ramaiah; Tajamul Hussain; Salman A. Alrokayan; Vijay Kumar Kutala (Journal of Community Genetics, 2016)

Modulation of digestive enzymes, GH, IGF-1 and IGF-2 genes in the teleost, Tilapia (Oreochromis mossambicus) by dietary curcumin - Sebastian J. Midhun; Damodaran Arun; Lincy Edatt; M. V. Sruthi; V. V. Thushara; Oommen V. Oommen; V. B. Sameer Kumar; Lekha Divya (Aquaculture International, 2016)

A New Fluorescent Sensor Based on Bisindolizine Derivative - Anitha I; Sheela Gopal M; Divya Thomas (Journal of Fluorescence, 2016)

A novel PR10 promoter from Erianthus arundinaceus directs high constitutive transgene expression and is enhanced upon wounding in heterologous plant systems - M. Chakravarthi; Divya P. Syamaladevi; P. Harunipriya; Sruthy Maria Augustine; N. Subramonian (Molecular Biology Reports, 2016)

Effects of concurrent physical and cognitive demands on muscle activity and heart rate variability in a repetitive upper-extremity precision task - Divya Srinivasan; Svend Erik Mathiassen; David M. Hallman; Afshin Samani; Pascal Madeleine; Eugene Lyskov (European Journal of Applied Physiology, 2016)

Assessing the tolerance of immobilized laccase from a salt-tolerant strain of Trichoderma viride Pers NFCCI-2745 to heavy metal ions, detergents and copper chelating agents - L. M. Divya; G. K. Prasanth; C. Sadasivan (International Journal of Environmental Science and Technology, 2015)

Combined effects of Piriformospora indica and Azotobacter chroococcum enhance plant growth, antioxidant potential and steviol glycoside content in Stevia rebaudiana - Divya Kilam; Monica Saifi; M. Z. Abdin; Abha Agnihotri; Ajit Varma (Symbiosis, 2015)

Physiological and Molecular Insights to Drought Responsiveness in Erianthus spp. - Sruthy Maria Augustine; Divya P. Syamaladevi; M. N. Premachandran; V. Ravichandran; N. Subramonian (Sugar Tech, 2015)

Short- and long-term reliability of heart rate variability indices during repetitive low-force work - David M. Hallman; Divya Srinivasan; Svend Erik Mathiassen (European Journal of Applied Physiology, 2015)

Overexpression of EaDREB2 and pyramiding of EaDREB2 with the pea DNA helicase gene (PDH45) enhance drought and salinity tolerance in sugarcane (Saccharum spp. hybrid) - Sruthy Maria Augustine; J. Ashwin Narayan; Divya P. Syamaladevi; C. Appunu; M. Chakravarthi; V. Ravichandran; Narendra Tuteja; N. Subramonian (Plant Cell Reports, 2015)

Ultraviolet and 5′Fluorodeoxyuridine Induced Random Mutagenesis in Chlorella vulgaris and Its Impact on Fatty Acid Profile: A New Insight on Lipid-Metabolizing Genes and Structural Characterization of Related Proteins - Josephine Anthony; Vijaya Raghavan Rangamaran; Dharani Gopal; Kumar T. Shivasankarasubbiah; Mary Leema J. Thilagam; Magesh Peter Dhassiah; Divya Shridhar M. Padinjattayil; VinithKumar N. Valsalan; Vijayakumaran Manambrakat; Sivakumar Dakshinamurthy; Sivaraman Thirunavukkarasu; Kirubagaran Ramalingam (Marine Biotechnology, 2015)

Erratum to: Marker assisted backcross breeding approach to improve blast resistance in Indian rice (Oryza sativa) variety ADT43 - Balakrishnan Divya; S. Robin; R. Rabindran; N. Senthil; M. Raveendran; A. John Joel (Euphytica, 2014)

Marker assisted backcross breeding approach to improve blast resistance in Indian rice (Oryza sativa) variety ADT43 - Balakrishnan Divya; S. Robin; R. Rabindran; S. Senthil; M. Raveendran; A. John Joel (Euphytica, 2014)

Automatic classification of protein structures using physicochemical parameters - Abhilash Mohan; M. Divya Rao; Shruthi Sunderrajan; Gautam Pennathur (Interdisciplinary Sciences: Computational Life Sciences, 2014)

Urgency for sustainable development in coastal urban areas with reference to weather pattern, land use, and water quality - A. M. Sheela; J. Letha; K. Swarnalatha; K. V. Baiju; Divya Sankar (Environmental Monitoring and Assessment, 2014)

Differential expression analysis of transcripts related to oil metabolism in maturing seeds of Jatropha curcas L. - Divya Chandran; H. M. Sankararamasubramanian; M. Ashok Kumar; Ajay Parida (Physiology and Molecular Biology of Plants, 2014)

Drought stress responses in crops - Arun K. Shanker; M. Maheswari; S. K. Yadav; S. Desai; Divya Bhanu; Neha Bajaj Attal; B. Venkateswarlu (Functional & Integrative Genomics, 2014)

XIAP inhibitor and antiestrogen embelin abrogates metastasis and augments apoptosis in estrogen receptor positive human breast adenocarcinoma cell line MCF-7 - K. R. Sumalatha; G. Abiramasundari; G. K. Chetan; T. Divya; G. Sudhandiran; M. Sreepriya (Molecular Biology Reports, 2014)

Production, purification and characterization of cholesterol oxidase from a newly isolated Streptomyces sp. - Ram Niwas; Vineeta Singh; Rajbir Singh; Divya Tripathi; C. K. M. Tripathi (World Journal of Microbiology and Biotechnology, 2013)

5′ Regulatory region of ubiquitin 2 gene from Porteresia coarctata makes efficient promoters for transgene expression in monocots and dicots - Anna Philip; Divya P. Syamaladevi; M. Chakravarthi; K. Gopinath; N. Subramonian (Plant Cell Reports, 2013)

From peptides to peptidomimetics: rational design of potential PKC-β II inhibitors - P. Sri Divya; Kapil Jain; M. Elizabeth Sobhia (Medicinal Chemistry Research, 2013)

Fe3O4-PEI-RITC Magnetic Nanoparticles with Imaging and Gene Transfer Capability: Development of a Tool for Neural Cell Transplantation Therapies - Humphrey H. P. Yiu; Mark R. Pickard; Cristina I. Olariu; Stephen R. Williams; Divya M. Chari; Matthew J. Rosseinsky (Pharmaceutical Research, 2012)

Molecular characterization of eight Indian Snakehead species (Pisces: Perciformes Channidae) using RAPD markers - Ajaz Ali Bhat; M. A. Haniffa; P. R. Divya; A. Gopalakrishnan; M. James Milton; Raj Kumar; Bilal Ahmad Paray (Molecular Biology Reports, 2012)

Effect of triadimefon: a triazole fungicide on oxidative stress defense system and eugenol content in Ocimum tenuiflorum L. - V. Divya Nair; R. Gopi; M. Mohankumar; J. Kavina; R. Panneerselvam (Acta Physiologiae Plantarum, 2012)

2D and 3D QSAR analyses to predict favorable substitution sites in anilino-monoindolylmaleimides acting as PKCβII selective inhibitors - P. Sri Divya; Baljinder K. Grewal; M. Elizabeth Sobhia (Medicinal Chemistry Research, 2011)

Prevalence of Very Low Numbers of Potential Pathogenic Isolates of Yersinia enterocolitica and Yersinia intermedia in Traditional Fast Foods of India - K. H. Divya; M. C. Varadaraj (Indian Journal of Microbiology, 2011)

Multiplicity of carbohydrate-binding sites in β-prism fold lectins: occurrence and possible evolutionary implications - Alok Sharma; Divya Chandran; Desh D. Singh; M. Vijayan (Journal of Biosciences, 2007)

Functional validation of a novel isoform of Na+/H+ antiporter from Pennisetum glaucum for enhancing salinity tolerance in rice - Dheeraj Verma; Sneh L Singla-Pareek; Divya Rajagopal; M K Reddy; S K Sopory (Journal of Biosciences, 2007)